2006
DOI: 10.1007/s11172-006-0279-y
|View full text |Cite
|
Sign up to set email alerts
|

The molecular and electronic structure features of silatranes, germatranes, and their carbon analogs

Abstract: Molecular geometries of fifty six metallatranes N(CH 2 CH 2 Y) 3 M-X and fifty six carbon analogs HC(CH 2 CH 2 Y) 3 M-X (M = Si, Ge; X = H, Me, OH, F; Y = CH 2 , O, NH, NMe, NSiMe 3 , PH, S) were optimized by the DFT method. Correlations between changes in the bond orbital populations, electron density ρ(r), electron density laplacian ∇ 2 ρ(r), |λ 1 |/λ 3 ratio, electronic energy density E(r), bond lengths, and displacement of the central atom from the plane of three equatorial substituents and the nature of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
(22 reference statements)
0
23
0
Order By: Relevance
“…Driven by the interest for germatranes, a remarkable effort in their synthetic chemistry was accomplished [6][7][8][9][10][11]. Chemical structure, molecular modeling and theoretical studies of these compounds [12][13][14][15][16] at different levels of theory, including correlated post-Hartee-Fock methods [16] allowed better understanding of the specificity of trans-annular N ? Ge bond and revealed the importance of interaction of Ge with all 5 substituents [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Driven by the interest for germatranes, a remarkable effort in their synthetic chemistry was accomplished [6][7][8][9][10][11]. Chemical structure, molecular modeling and theoretical studies of these compounds [12][13][14][15][16] at different levels of theory, including correlated post-Hartee-Fock methods [16] allowed better understanding of the specificity of trans-annular N ? Ge bond and revealed the importance of interaction of Ge with all 5 substituents [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical structure, molecular modeling and theoretical studies of these compounds [12][13][14][15][16] at different levels of theory, including correlated post-Hartee-Fock methods [16] allowed better understanding of the specificity of trans-annular N ? Ge bond and revealed the importance of interaction of Ge with all 5 substituents [13][14][15]. Biological activity of germatranes that is closely bound with the substitution character at Ge was extensively studied [1,[4][5][6]17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Si bonding we estimated the experimental and theoretical k 1 /k 3 ratio values in 9 and 5 which are equal to 0.346, 0.304 and 0.227, respectively. These values can be considered as extent of covalent character of the coordination bonds in hypervalent organosilicon compounds [16,21]. The k 1 /k 3 obtained fall within the range typical for most of silatranes.…”
Section: Chemical Bonding In Crystal Of 5 Andmentioning
confidence: 51%
“…The choice of PW91-PW method instead of standard B3LYP and MP2 calculations of isolated molecules is caused by necessity to take into account the crystal packing. The analysis of literature concerning pentacoordinated silicon species has shown that interatomic Si-N distances in isolated molecules [16][17][18] are in most cases exceed the experimental values (revealed by X-ray diffraction) by 0.2-0.3 Å, that makes difficult direct comparison experimental and theoretical results. Unfortunately, the disorder of C1 and C2 atoms in compound 3 made impossible the experimental study and quantum chemistry calculation of its crystal structure.…”
Section: Chemical Bonding In Crystal Of 5 Andmentioning
confidence: 96%
See 1 more Smart Citation